The value system of Polish drivers in the context of road safety - a research report - Paulina Michalska; Anna Szymanik-Kostrzewska (Nofer Institute of Occupational Medicine, 2020)
Background The main objective of the research was to describe the hierarchy of values of drivers, with particular emphasis on the values relevant to road safety - personal safety, social security, humility and adaptation to rules, as well as the relationship between them and the number of accidents and collisions in which drivers participated. The additional goal was to determine the significance of variables (age, sex, seniority in driving, education, staying in a relationship, the number of children) for the hierarchy of drivers' values. Material and Methods The Portrait Value Questionnaire (PVQ) by Shalom Schwartz, in the Polish adaptation by Cieciuch, was applied. The research was conducted on a group of 704 drivers of both sexes (356 women and 348 men), aged: 18-77 years, of whom 303 people were asked about the number of accidents and collisions in which they had participated or which they had caused. Results The drivers that took part in the research valued kindness and safety to a large extent, but the need for self-determination, especially in men and young drivers, prevailed over the value of discipline. The number of accidents and collisions turned out to be important for the valuation of security in the social context, with the observed interdependence being bi-directional. Among the variables controlled for the hierarchy of values, drivers' age and gender of were of particular importance. Conclusions The hierarchy of values of the examined drivers indicates the appreciation for kindness and safety, to a large extent, and the value of discipline (humility and respect for rules), but the need for self-determination (self-management), especially in men and young drivers, was found to prevail. The main limitation of this research was the data collection method based solely on self-reports, as a result of which the obtained results may be burdened with the need to gain social approval. Med Pr. 2020;71(2):137-52